Does brand anthropomorphism and brand intimacy matter to assess consumers' engagement successfully? - Thanh Nguyen Ngoc Dan; Phuc Ngo Trong (Cogent Business & Management, 2023)
This study aims to analyze the impact of Brand Anthropomorphism and Intimacy on the attachment between consumers and the Samsung electronic technology brand. Data were collected by convenience sampling from 357 respondents through an internet survey, using SPSS 25 and AMOS 25 software along with CB-SEM (Covariance-based SEM) analysis technique to evaluate the relationship between structures. Research results show that Brand Anthropomorphism has a direct impact on Intimacy and Brand Engagement, and Intimacy is the mediator between Brand Anthropomorphism and Brand Engagement. In addition, the research results show that in Vietnam, specifically, Ho Chi Minh City, the Brand Anthropomorphism factor in the Samsung technology brand market consists of only three components instead of four components like other brands' previous research. In addition, this study demonstrates the role of Brand Anthropomorphism in the context of the electronic technology market, which marketing managers can deploy to achieve effective engagement between consumers and brands.
Keywords: 650; brand anthropomorphism; brand engagement; electronic technology brand; intimacy